2020
DOI: 10.31763/businta.v4i2.204
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide mobile wallet: a futuristic cashless system

Abstract: The proliferation of the internet led to the emergence of new technology. Nowadays, many activities can be done online, such a payment. After Mobile Banking was introduced publicly, a new method for payment called mobile wallet that uses mobile application as a device appears. The ease caused by this technology should be the main reason for implementing this system on to daily basis. Nevertheless, in various countries, the usage rate of the cashless system remains uneven, caused by many factors, both from inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…In this study, we analyze survey data from a representative sample of the Norwegian population to investigate whether we find the same relationships in a Northern European country with a population that has a higher level of financial literacy, is more digitally advanced than the US population, 1 and is one of the countries furthest along in the world in becoming a cashless society (Mumtaza et al, 2020 ; Wewege & Thomsett, 2019 ). In this article, we include three different types of digital payment technologies, not just mobile payments as in US studies, and look at all adult generational groups.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…In this study, we analyze survey data from a representative sample of the Norwegian population to investigate whether we find the same relationships in a Northern European country with a population that has a higher level of financial literacy, is more digitally advanced than the US population, 1 and is one of the countries furthest along in the world in becoming a cashless society (Mumtaza et al, 2020 ; Wewege & Thomsett, 2019 ). In this article, we include three different types of digital payment technologies, not just mobile payments as in US studies, and look at all adult generational groups.…”
mentioning
confidence: 95%
“…Recent studies have worryingly concluded that mobile payment users in the USA are at a higher risk of financial mismanagement than nonusers. In a world that moves quickly in the direction of forsaking the use of cash for digital financial tools (Mumtaza et al, 2020 ; Wewege & Thomsett, 2019 ), fueled even more by the COVID-19 pandemic (Shearman, 2020 ; eMarketer, 2021 ), it is important to investigate whether these US results are generalizable for other countries and generations. Gaining this knowledge could be imperative in taking measures to help stifle this financial mismanagement.…”
mentioning
confidence: 99%
“…Urhie et al ( 2021 ) found mobile banking to promote cashless payments. In Singapore, the usage of cashless payments was high, but Singaporeans still prefer cash and card payments (Mumtaza et al 2020 ). There is no conclusive evidence that diffusion from cash to cashless payment would increase the usage of internet and mobile banking services.…”
Section: Cashless Payment Internet Banking and Mobile Bankingmentioning
confidence: 99%
“…Although mobile payments have been around for some time, Kaur et al (2020) say mobile wallets have contributed a new and more versatile way to process payments via the internet. Additionally, Mumtaza et al (2020) argue that mobile wallets can be a real alternative to cash, given how easy they are to use and the positive impact they have on cashless transactions.…”
Section: Box 2 How the Use Of Mobile Wallets Has Evolvedmentioning
confidence: 99%
“…On the other hand, the factors that determine the use of mobile wallets and mobile payments by the population have been identified in the literature. Ease of access and use, perceived usefulness and security, efficiency, transparency, limited access to banking services and the high cost of transfer services are the most predominant ones (see Iman, 2018;Karsen et al, 2019;Kaur et al, 2020;Mumtaza et al, 2020). However, the use of mobile wallets tends to be limited and mixed in developing countries (see Kaur et al, 2020;Mumtaza et al, 2020), where differences in internet access, literacy, access to banking services and infrastructure determine this heterogeneity.…”
Section: Box 2 How the Use Of Mobile Wallets Has Evolvedmentioning
confidence: 99%